Holocene land–sea climatic links on the equatorial Pacific coast (Bay of Guayaquil, Ecuador). (April 2016) - Seillès, Brice; Sánchez Goñi, Maria Fernanda; Ledru, Marie-Pierre; Urrego, Dunia H; Martinez, Philippe; Hanquiez, Vincent; Schneider, Ralph
We analyzed the pollen content of a marine core located near the Bay of Guayaquil in Ecuador to document the link between sea surface temperatures (SSTs) and changes in rainfall regimes on the adjacent continent during the Holocene. Based on the expansion/regression of five vegetation types, we observe three successive climatic patterns. In the first phase, between 11, 700 and 7700 cal. yr BP, the presence of a cloud (Andean) forest in the mid altitudes and mangroves in the estuary of the Guayas basin, were associated with a maximum in boreal summer insolation, a northernmost position of the Intertropical Convergence Zone (ITCZ), a land–sea thermal contrast, cloud dripping, and dry edaphic conditions. Between 7700 and 2850 cal. yr BP, the expansion of the coastal vegetation and the regression of the mangrove indicate a drier climate with weak ITCZ and low El Niño Southern Oscillation (ENSO) variability while austral summer insolation gradually increased. The interval between 4200 and 2850 cal. yr BP was marked by the coolest and driest climatic conditions of the Holocene because of the weak influence of the ITCZ and a strengthening of the Humboldt Current. After 2850 cal. yr BP, high variability and amplitude of the Andean forest changes occurred when ENSO frequency and amplitude increased, indicating high variability in land–sea connections. The ITCZ reached the latitude of Guayaquil only after 2500 cal. yr BP inducing the bimodal precipitation regime we observe today. Our study shows that besides insolation, the ITCZ position, and ENSO frequency, changes in eastern equatorial Pacific SSTs play a major role in determining the composition of the ecosystems and the hydrological cycle of the Ecuadorian Pacific coast and the Western Cordillera in Ecuador.